2005
DOI: 10.4028/www.scientific.net/msf.495-497.1615
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Anisotropy and Texture Evolution of Rolled AZ3l Magnesium Alloys

Abstract: The plastic anisotropy was measured for a commercial AZ31 magnesium sheet and compared with results from a model calculation using a self consistent viscoplastic model. The anisotropy of plastic flow stresses can be explained by the off-basal character of the texture and the activation of the <a> prismatic slip in addition to the basal, <c+a> pyramidal slip and the > < 1 1 01 } 2 1 01 { twinning system. The strain anisotropy r ( r = ew/et ; ew, et – strains in width and thickness directions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Figure 11 compares the predicted R-values along different loading paths, where the R-value evolves significantly with straining under tension (Figure 11a). The variation in R-value with imposed tensile straining is confirmed by the experimental works on magnesium alloys at room temperature [11,49,50,51,52,53]. It is found that the predicted R-values under in-plane compressions is negative at small strain (Figure 11b).…”
Section: Resultssupporting
confidence: 68%
“…Figure 11 compares the predicted R-values along different loading paths, where the R-value evolves significantly with straining under tension (Figure 11a). The variation in R-value with imposed tensile straining is confirmed by the experimental works on magnesium alloys at room temperature [11,49,50,51,52,53]. It is found that the predicted R-values under in-plane compressions is negative at small strain (Figure 11b).…”
Section: Resultssupporting
confidence: 68%